Innovations in Practice: Adolescent Mentalization‐Based Integrative Therapy (AMBIT) – a new integrated approach to working with the most hard to reach adolescents with severe complex mental health needs. Issue 1 (4th May 2012) - Bevington, Dickon; Fuggle, Peter; Fonagy, Peter; Target, Mary; Asen, Eia
<x xml:space="preserve">Abstract</x> Background 'Hard to reach' young people are associated by virtue of their serious, multiple, and complex needs, the difficulty of delivering effective help to them, and their poor long‐term outcomes. There is a lack of published evidence relating to the effectiveness of interventions directed at this group. Method We review these concerns and the options available to service commissioners and clinicians seeking, if not an evidence‐based approach then at least an evidence‐oriented one. A mentalization‐based multimodal intervention (AMBIT) is briefly described, proposing a new kind of specialist practitioner and taking a radically different approach to treatment manualization. Results A brief description is given of the different settings in which AMBIT is currently being developed, deployed, and evaluated, and of lessons learned. Conclusions AMBIT offers promise as an evolving 'open source' framework supporting development of evidence‐based local practice in chaotic complex settings.